Oxygen availability affects exercise capacity, but not neuromuscular fatigue characteristics of knee extensors, during exhaustive intermittent cycling - Girard, O.; Buchheit, M.; Goodall, S.; Racinais, S. (European Journal of Applied Physiology, 2021)
Purpose: To compare the effects of different hypoxia severities on exercise capacity, cardio-respiratory, tissue oxygenation and neuromuscular fatigue characteristics in response to exhaustive intermittent cycling. Methods: Eleven well-trained cyclists, repeated supra-maximal cycling efforts of 15 s (30% of anaerobic power reserve, 609 ± 23 W), interspersed with 45 s of passive rest until task failure. The exercise was performed on separate days in normoxia (SL; simulated altitude/end-exercise arterial oxygen saturation = 0 m/~ 96%), moderate (MH; 2200 m/~ 90%) and severe (SH; 4200 m/~ 79%) hypoxia in a cross-over design. Neuromuscular tests, including brief (5 s) and sustained (30 s) maximal isometric voluntary contractions of the knee extensors, were performed at baseline and exhaustion. Results: Exercise capacity decreased with hypoxia severity (23 ± 9, 16 ± 6 and 9 ± 3 cycle efforts in SL, MH and SH, respectively; P < 0.001; Eta2 = 0.72). Both cerebral (P < 0.001; Eta2 = 0.86) and muscle (P < 0.01; Eta2 = 0.54) oxygenation decreased throughout the exercise, independent of condition (P = 0.45; Eta2 = 0.14). Compared to SL, muscle oxygenation was globally lower in MH and SH (P = 0.011; Eta2 = 0.36). Cardiovascular solicitation neared maximal values at exhaustion in all conditions. Peak twitch amplitude with single and paired electrical stimuli (P < 0.001; Eta2 = 0.87), maximal torque (P < 0.001; Eta2 = 0.48) and voluntary activation measured using transcranial magnetic stimulation (P = 0.034; Eta2 = 0.31) during brief and sustained MVCs were all reduced at exhaustion, independent of condition (P = 0.196; Eta2 = 0.15). Conclusion: Despite reduced exercise capacity with increasing severity of hypoxia during exhaustive intermittent cycling, neuromuscular fatigue characteristics were not different at task failure and cardiovascular solicitation neared maximum values.